ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK BERDASARKAN TAKSONOMI SOLO PADA KELAS VIII SMPN 1 PADANG - SHONIA PUTRI HARDINA (Departemen Matematika, 2018)
One of the goals of learning mathematics in schools is that students have good mathematical problem-solving abities. Mathematical problem-solving abilities of students is the cognitive abilities of students in solving problems, one of which can be seen from the answers given by students to the problem given. One theory that can classify students' answers in solving mathematical problems is the Taxonomy Structure of the Observed Learning Outcome (SOLO).SOLO Taxonomy classifies the level of ability of students' answers to problems into five levels, namely pre-structural level, unistructural level, multistructural level, relational level, and extended abstract level. This study aims to describe and analyze students' mathematical problem solving abilities based on SOLO taxonomy in class VIII of SMP Negeri 1 Padang.The type of research conducted is descriptive with the taking of research subjects using purposive sampling technique. Data collection techniques used are tests, interviews, and observations while the analytical techniques used for this research are descriptive analysis and data triangulation. The results of the research on mathematical problem-solving abilities of students based on SOLO taxonomy shows that students in the upper group have mathematical problem-solving abilities at the relational level, students who are in the middle group have mathematical problem-solving abilities at the unistructural, multistructural level, and relational level, as well as students who are in the lack groups have mathematical problem-solving abilities at the level of prestructural and unistructural level. Keywords - mathematical problem-solving abilities, solo taxonomy